Pilot study investigating diagnostic utility of serum MMP-1 and TGF-β1 in asthma in 'real world' clinical practice in India. Issue 4 (17th February 2021) - Prabha, Aswani; Lokesh, Komarla Sundararaja; Chaya, S K; Jayaraj, B S; Malamardi, Sowmya; Subbarao, M V S S T; Beck, Sarah C; Krishna, Mamidipudi Thirumala; Mahesh, Padukudru Anand
Abstract : Aims: At a tissue level, matrix metalloproteinase-1 (MMP-1) and transforming growth factor-beta 1 (TGF-β1) contribute to allergic airway inflammation, tissue remodelling and disease severity in asthma via different pathways. Their peripheral blood levels and role in diagnosis and therapeutic monitoring has not been adequately explored. We investigated the association between MMP-1 and TGF-β in moderate and severe persistent asthma and evaluated their performance characteristics by constructing receiver operating characteristic curves. Methods: Serum MMP-1 and TGF-β1 were measured using ELISA in 75 adults; moderate persistent asthma (n=25), severe persistent asthma (n=25) and healthy community controls (n=25). Severity of asthma was determined as per Global Initiative for Asthma guidelines. Subjects were followed up for 3 months and treatment responsiveness was assessed by spirometry and symptom response. Results: Serum MMP-1 and TGF-β1 were significantly elevated in asthmatics compared with controls (p<0.0001 and p<0.01). While serum MMP-1 was elevated in severe asthma compared with moderate asthma (p<0.05), TGF-β1 was lower in severe asthma compared with moderate asthma (p<0.05). The performance characteristics of serum MMP-1 and TGF-β1 were promising in this cohort with sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of 82%, 100%, 100% and 99% and 62%, 100%, 100% and 97.8%, respectively; sensitivity of MMP-1 being superior. Conclusion: This pilot study showed that serum MMP-1 and TGF-β1 levels are elevated in chronic asthma and may serve as a useful adjunct in differentiating moderate from severe asthma. A large multicentre study in well characterised cohort of asthmatics is warranted to investigate their role in diagnosis and therapeutic monitoring.